IMPLEMENTATION AND PERFORMANCE ANALYSIS OF MININET-BASED TESTBED FOR P4 PROGRAMMABLE DATA PLANE - Devindira Hasnaa, Larastya
The increasing use of the internet in various fields has led to the continuous development of network technologies. SDN (Software-Defined Networking) is one approach to address the challenges associated with managing larger and more complex networks by separating the control plane and data plane. The programmable data plane is an effort to enhance the flexibility of the data plane by determining how packet processing in the data plane should be performed. One way to achieve this is by using the P4 language. Currently, the development of programmable data plane using P4 is still at a low level of technological maturity. Therefore, in an effort to improve the technological maturity of P4, a testbed for SDN with a P4-based Mininet is developed, along with a performance analysis of various scenarios with different levels of complexity. The selected scenarios for this testbed include Forwarding as a simple scenario, as well as MPLS Basic and MPLS Stacked as advanced scenarios. Based on the performance testing conducted, the value of delay is influenced by the complexity of the executed P4 programs. Jitter, as the variance of delay, produces relatively small values in all scenarios, indicating that the delay in each scenario can be considered fairly stable. The throughput achieved in all scenarios is still far from the allocated bandwidth. This is due to the allocation of bandwidth exceeding the specifications of the server running Mininet, resulting in increased CPU usage and suboptimal packet delivery. As a result, a relatively high packet loss rate is observed.